Implementation of Project-Based Learning in Deep Learning by Early Childhood Education Teachers in the Bunga Tanjung Cluster, Bengkulu City - Herlina, Yuni; Sukirdi, Sukirdi; Haryono, Mimpira (Universitas Dehasen Bengkulu, 2025)
This community service activity aims to improve the competency of early childhood education (PAUD) teachers in Gugus Bunga Tanjung, Bengkulu City, in implementing project-based learning (PjBL) as part of the in-depth learning program in accordance with the Independent Curriculum. Implementation methods included initial observation, training in developing project-based lesson plans (RPP), mentoring in teaching practice, and reflection on implementation results. This activity involved 30 teachers who participated in a series of training and mentoring sessions throughout the program. Results demonstrated improved teacher skills in designing and implementing contextual projects, active participation of children in the learning process, and character strengthening through meaningful learning experiences. The implementation of PjBL has proven relevant to the principles of the Independent Curriculum and has had a positive impact on the quality of classroom learning. This activity recommends the continued development of project ideas appropriate to the local context, resource support from schools, and the formation of a learning community for early childhood teachers to share best practices in PjBL implementation.